De différents types de jonction dans les series synonymiques choisies - Tkaczyk, Magdalena (Studia Romanica Posnaniensia, 2007)
In the article we discuss semantic connectivity of set of synonymous adjectives series. We present models of connection of selected types of French and Polish adjectives, frequency of their appearance and methods of realization in individual synonymous series.